2012
DOI: 10.1093/carcin/bgs234
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mammalian target of rapamycin as a direct target of fenretinide both in vitro and in vivo

Abstract: N-(4-hydroxyphenyl) retinamide (4HPR, fenretinide) is a synthetic retinoid that has been tested in clinical trials as a cancer therapeutic and chemopreventive agent. Although 4HPR has been shown to be cytotoxic to many kinds of cancer cells, the underlying molecular mechanisms are only partially understood. Until now, no direct cancer-related molecular target has been reported to be involved in the antitumor activities of 4HPR. Herein, we found that 4HPR inhibited mammalian target of rapamycin (mTOR) kinase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…5). The chosen dose of HPR (40 mg/kg), shown previously to be effective when used three times per week to slow down growth of A549 xenograft mouse model [21], was found not curative with mouse SCCVII tumors upon use in a single dose. However, this HPR treatment produced a significant improvement in tumor cure rates when combined with a PDT dose that was marginally curative when used alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5). The chosen dose of HPR (40 mg/kg), shown previously to be effective when used three times per week to slow down growth of A549 xenograft mouse model [21], was found not curative with mouse SCCVII tumors upon use in a single dose. However, this HPR treatment produced a significant improvement in tumor cure rates when combined with a PDT dose that was marginally curative when used alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4-HPR is known to have multiple targets, some of which overlap with naturally occurring retinoids (39). These include the retinoic acid receptors (RARs) (53,54), retinol-binding proteins (RBPs) (39,55), mammalian target of rapamycin (mTor) (56), and dihydroceramide desaturase (DES) (29,31,57,58), among others. Because we found that all-trans retinoic acid (ATRA) and other analogs of ATRA did not inhibit DENV-2 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both FEN exposure and dihydroceramides accumulation can initiate cellular survival pathways such as the ER stress response and autophagy induction [39,[44][45][46]. FEN has also been reported to inhibit the kinase activity of mammalian target of rapamycin (mTOR) both in vitro and in vivo [47]. This may possibly occur through the direct binding of FEN to the ATP pocket of mTOR, based on computer modelling of the crystal structure of PI3K-delta [47].…”
Section: Mtor and Autophagy A Cell Survival Mechanismmentioning
confidence: 99%
“…FEN has also been reported to inhibit the kinase activity of mammalian target of rapamycin (mTOR) both in vitro and in vivo [47]. This may possibly occur through the direct binding of FEN to the ATP pocket of mTOR, based on computer modelling of the crystal structure of PI3K-delta [47]. Since mTOR is a key inhibitor of autophagy, inhibition of mTOR by FEN may result in an increase in autophagy induction.…”
Section: Mtor and Autophagy A Cell Survival Mechanismmentioning
confidence: 99%